Pelatihan pembuatan pupuk organik bagi petani padi di Desa Bonto Macinna Kecamatan 1,2 Gantarang Kabupaten Bulukumba - Ramli Umar; Uca Uca (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Rice straw has not been assessed as a product thathas economic value. In a straw-intensive farming system, it isoften regarded as crop residues that disturb land managementand rice cultivation. Farmers burn straw at a place a few daysafter the rice is harvested. The main purpose of straw-burningstraw is to get rid of straw from the rice fields in a practicalway. Therefore, it is necessary to conduct training for thecommunity so that they can utilize rice straw into organicfertilizer. This community service activity was carried out for3 days in a row. The result of this training is that the farmingcommunity in Bonto Macinna village is able to manage orutilize rice straw into organic fertilizer.